Peningkatan Kompetensi Statistik Mahasiswa UIN Mataram Melalui Pelatihan Praktis Analisis Varians (ANOVA) Menggunakan Software JASP Untuk Analisis Data Tugas Akhir - Muhammad Ghazali; Muhammad Muhammad; Ita Fitriati (BALE LITERASI, 2026)
This community service program carried the theme “Enhancing the Statistical Competence of UIN Mataram Students Through Practical Training on Analysis of Variance (ANOVA) Using JASP Software for Final Project Data Analysis.” The program was delivered in the form of training for final-year students as well as students who had previously taken courses in Statistics and Research Methodology. The activity took place in the computer laboratory at the Research Center Building, Campus 2 of UIN Mataram, with a total of 30 participants. Most participants were fifth- or seventh-semester students who were currently working on or preparing to begin their undergraduate thesis or final project. The training was conducted offline. The stages of the activity included an opening session, material presentation, hands-on training, a discussion or Q&A session, and finally, a closing session. After the training, the service team distributed a questionnaire to evaluate the program. The results indicated a significant improvement in students’ understanding of data analysis, particularly in comparative cases involving more than two groups, which can be analyzed using ANOVA. The paired t-test results showed a highly significant increase in participants’ scores after the training. The average pretest score was 28.67 (pretest SD ? 6.29), while the average posttest score increased to 76.17 (posttest SD ? 8.78). The mean difference (posttest ? pretest) of +47.50 reflects a substantial improvement. The paired t-test yielded t(29) = ?27.03, p < .001 (the test was conducted on the difference between pretest and posttest scores), indicating that the improvement was statistically significant. Thus, both statistically and practically, the ANOVA training using JASP proved to be effective in enhancing participants’ analytical skills.